High grade metamorphism in the Bundelkhand massif and its implications on Mesoarchean crustal evolution in central India - Singh S.P.; Dwivedi S.B. (My University, 2025)
The Bundelkhand Gneissic Complex (BnGC) in the central part of the Bundelkhand massif preserves a supracrustal unit which includes pelitic (garnet-cordierite-sillimanite gneiss, garnet-sillimanite gneiss, biotite gneiss and garnet-biotite gneiss) and mafic (hornblende-biotite gneiss and garnetiferous amphibolite) rocks. Granulite facies metamorphism of the complex initiated with breaking down of biotite to produce garnet and cordierite in the pelitic gneisses. Geothermobarometric calculations indicate metamorphic conditions of 720◦C/6.2 kbar, followed by a retrograde (687◦C/4.9 kbar) to very late retrograde stages of metamorphism (579◦C/4.4 kbar) which is supported by the formation of late cordierite around garnet. The P-T conditions and textural relations of the garnet-cordierite-bearing gneiss suggest a retrograde cooling path of metamorphism. © Indian Academy of Sciences.